Identifikasi Kesalahan Siswa dalam Menyelesaikan Soal Trigonometri Kelas X SMA Negeri 1 Kasongan - Stefanus Kristian Evan; Pantur Pandiangan; Sugiharto . (JURNAL PENDIDIKAN, 2023)
This research was motivated by the SMA Negeri 1 Kasongan school which never identified student errors in solving trigonometry problems. This type of research is descriptive with quantitative and qualitative approaches. This research was conducted in the even semester of the 2021/2022 academic year. Subjects are students of class X SMA Negeri 1 Kasongan for the academic year 2021/2022. Data collection techniques used are tests and interviews conducted face-to-face at school. The research instrument used was a test sheet consisting of 3 items of description. The test questions in this study were reviewed by three raters. The types of errors made by students in solving trigonometry problems are: Fact Error (A1) most students miswrite the term (name) or symbol/notation used in trigonometry material, Concept Error (A2) students do not understand abstract ideas in trigonometry material so that students cannot solve trigonometry problems, and Operational Errors (A3) students work on problems not according to the correct problem solving procedure, Principle Errors (A4) students do not understand the relationship between several facts and concepts and theorems associated with relations or operations so that errors occur in the completion process and result. The factors that cause students to make mistakes in solving trigonometry problems in the sub-material of trigonometry comparisons in right triangles, namely: Knowledge, in the form of lack of facts, truths or information obtained by students regarding the material that has been studied from simple to difficult material. Understanding, in the form of a lack of students' ability to understand the content of the material. Application, in the form of a student's lack of ability to apply the material that has been learned in new situations and involves the use of rules or principles.